(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the article possibility of predictions about activation and expected movements of landslides and about their formulation in the landslide slopes, by parameters of geophysical fields and underground water composition are shown. Some researches in this field are still in development.